Representasi Prosesi Pernikahan Dalam Puisi W.S. Rendra Berjudul "Undangan", "Nyanyian Para Malaikat", Dan "Kakawin Kawin". - Lintang Milatama Sugianto (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
marriage is the process of binding sacred promises between men and women. Marriage is a sacred event through which several steps pass. The steps in the wedding are referred to as the wedding procession. Human feelings can be represented through verses of poetry, stories in novels, lyrics in songs, and conversations in films. Literary works are able to express all human problems and feelings. The type of research used is qualitative descriptive research using the method of Comparative Literature. The data source used is a collection of poems by W.S Rendra includes poems 'invitation’,' Song Of The Angels’, and 'Kakawin Kawin' in the book four collections of poems. These three works were chosen because they have a connection to the wedding procession. Research techniques used are data collection, data analysis, and data inference. Based on the results of the study it can be concluded that there is a wedding procession represented through the poem ’invitation’,’Song Of The Angels’, and ’Kakawin Kawin’. In the poem 'invitation ’and’ Song Of The Angels', both set in a church, and are going through the process of marriage. Meanwhile, the poem 'Kakawin Kawin' is set in the House of the late bride. The difference lies in different situations but each poem represents the wedding procession differently.